Laser-cutting of thin electrical sheets for the flexible production of electric drives Laserschneiden in der elektroblechfertigung: Flexible und produktive produktion dünner elektrobleche für elektrische traktionsmotoren in elektrofahrzeugen - Franke, Jörg; Schmidt, Michael; Hubert, Markus; Risch, Florian; Tremel, Jan; Hofmann, Benjamin (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2012)
The production of electric drives is put to a test. Known process chains are questioned by an extended group of industrial participants and new materials in the stator and rotor increasingly challenge traditional processes such as interlocking. Although laser cutting of electrical sheets has already been used in many flexible productions for a long time, in a direct benchmark it cannot be considered at the same level with high-performance punching techniques. Therefore, by the research group of the Bavarian Technology Center for Electric Drives (E|Drive-Center) of the Institute for Factory Automation and Production Systems, Friedrich-Alexander-University Erlangen-Nuremberg, rationalization effects in laser cutting and an increased level of automation are addressed. The special advantages of using high brightness lasers for the cutting process are investigated together with the Bayerisches Laserzentrum GmbH and the Institute for Photonic Technologies at the FAU.
CRIS-Team Scopus Importer:2024-08-06